2018
DOI: 10.1016/s2095-3119(17)61847-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs associated with cadmium concentration in rice grains

Abstract: Cadmium (Cd) contamination in rice has been a hot topic of research because of its potential risk to human health. In this study, a double haploid (DH) population derived from Zhongjiazao 17 (YK17) (an early-season indica cultivar)×D50 (a tropical japonica cultivar) was used to identify quantitative trait loci (QTLs) associated with Cd concentration in brown rice (CCBR) and Cd concentration in milled rice (CCMR). Continuous and wide variation for CCBR and CCMR were observed among the DH population. Correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 38 publications
0
7
1
Order By: Relevance
“…Quantitative trait locus (QTL) mapping, a powerful tool to study multivariate genes for complex agronomic traits, has been successfully used to identify loci that control Cd accumulation in rice ( Hu et al, 2018 ). Several QTLs for Cd tolerance have been identified through different genetic populations and phenotypic analysis methods.…”
Section: Genetic Variations and Qtls In Absorption And Distribution O...mentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative trait locus (QTL) mapping, a powerful tool to study multivariate genes for complex agronomic traits, has been successfully used to identify loci that control Cd accumulation in rice ( Hu et al, 2018 ). Several QTLs for Cd tolerance have been identified through different genetic populations and phenotypic analysis methods.…”
Section: Genetic Variations and Qtls In Absorption And Distribution O...mentioning
confidence: 99%
“…QTL analysis of Cd accumulation using an F2 population from Anjana Dhan and Nipponbare identified a QTL on chromosome 7 with a significant effect on Cd accumulation, explaining 85.6% of the phenotypic variation in Cd concentration in the shoots of the F2 population ( Ueno et al, 2009b ). Hu et al identified certain QTLs related to Cd content in brown rice (CCBR) and Cd content in milled rice (CCMR) using a double haploid (DH) population of Zhongjiadao 17 × D50, of which qCCBR2-1 / qCCBR2-2 and qCCBR9-1 / qCCBR9-2 were found to be responsible for CCBR, whereas qCCMR5-1 / qCCMR5-2 were found to be responsible for CCMR in several fields and pot experiments ( Hu et al, 2018 ). Zhao et al detected 14 Cd accumulation QTLs in rice grains from 312 rice accessions by a genome-wide association study (GWAS) ( Zhao et al, 2018 ), of which 3 QTLs were first identified in this study, and 4 QTLs were the previously cloned genes ( OsNRAMP1 , OsNRAMP5 , OsHMA3 , and LCD ) that mediate Cd accumulation in rice ( Miyadate et al, 2011 ; Shimo et al, 2011 ; Takahashi et al, 2011 ; Sasaki et al, 2012 ).…”
Section: Genetic Variations and Qtls In Absorption And Distribution O...mentioning
confidence: 99%
“…Genetic and physiological investigations suggest that the major QTL detected on the long arm of chromosome 11 is responsible for the specific translocation of Cd from the roots to the shoots [52]. Chromosome 7 harbors several putative metal transporters encoding genes such as OsZIP8, OsHMA3, and OsNramp1 [42,56]. Three major QTL (qCCBR1-1, qCCBR4-2, and qCCBR9-1) associated with Cd concentration in brown rice and another one named qCCMR11-2 in the milled rice explained more than 20% of the phenotypic variance respectively.…”
Section: Current Trends In Breeding Programsmentioning
confidence: 99%
“…Using 46 chromosome segment substitution lines (CSSLs), Abe et al (2013) detected a major QTL, qlGCd3, on the long arm of chromosome 3, which was responsible for reduced Cd concentration in rice grains. Using 204 RILs, Hu et al (2018) identified 22 QTLs affecting the accumulation of Cd, Cu, Fe, Mn, and Zn in brown rice, among which qCd5 was a novel QTL that regulated low Cd accumulation. Luo et al (2018) identified a QTL named CAL1 (Cd accumulation in leaf 1) on chromosome 2 using a doubled haploid (DH) population derived from TN1 and CJ06.…”
Section: Identification Of Molecular Markers For Low CD Accumulation mentioning
confidence: 99%